A late onset cutaneous rash associated with COVID-19: a pediatric case. - Colonna, C.; Monzani, N.A.; Ponziani, A.; Zussino, M.; Gelmetti, C.; Restano, L. (European Journal of Pediatric Dermatology, 2021)
The pandemic infection caused by the new coronavirus SARS-CoV-2 (COVID-19) has been associated, like numerous other viral infections, with heterogeneous skin manifestations. The latter are present both in severe forms, where they are less important compared to the involvement of internal organs, and in mild, poorly symptomatic cases where they may be important for tracking the disease. The current report describes two brothers with an atypical eruption associated with COVID-19 characterized by prevalent involvement of the face and very late onset, two months after modest systemic symptoms.